Fire Safety Assessment of a Typical Sports Hall Building Based on Fire Dynamics and Crowd Movement Models - Thareq, Achmad Efrizal; Purnomo, Dwi Marhaendro Jati; Auzani, Ahmad Syihan; Nugroho, Yulianto Sulistyo; Santoso, Muhammad Agung (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2024)
Fire risk analysis is one of the essential components of building design to ensure the safety of occupants and properties in case of fires. Currently, the Ministry of Public Works and Housing Regulation No. 20/PRT/M/2009 provides guidelines for conducting a fire risk analysis, however, without a clear consideration of fire dynamics in the estimation of the fire risk level. In this work, we investigate the fire safety aspects of a typical sports hall buildings by a fire dynamics deterministic model (Fire Dynamics Simulator (FDS) of the National Institute of Science and Technology, USA) and crowd movement model for occupant evacuation (Pathfinder of Thunderhead Engineering). Systematic investigations were made on the effects of the fire growth category and smoke extraction system on the Available Safe Egress Time (ASET). The results of ASET were then compared to the Required Safe Egress Time (RSET) which is obtained from the evacuation model. Our results suggest that ASET decreases exponentially with fire growth rate, especially from slow to medium growth rate. The fire growth rate significantly affects the acceptable fire risk of ASET longer than RSET. Occupant capacity, fire management systems, and smoke extraction systems play important roles in reducing fire risk. However, as the fire growth rate increases, the effects of smoke extraction in maintaining safe conditions diminish. This study provides recommendations to reduce risks to the occupants in case of fire, contributing to the considerations of the design and management of a typical sports hall building.